2018
DOI: 10.14233/ajchem.2018.21004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Anticancer Activity of Macaranga hosei Leaves

Abstract: INTRODUCTIONMacaranga is one genus of the family Euphorbiaceae comprising of ± 300 species. In Indonesia, this plant known as "Mahang". The distribution of Macaranga plants is relatively wide, other than Indonesia, can also be found in Africa, Madagascar, Asia, the east coast of Australia and the Pacific islands [1].According to previous studies, phenolics such as flavonoids and stilbenoids can be isolated from this genus. The uniqueness of flavonoids and stilbenoids from this genus is the presence of terpenoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The UV spectrum showed absorption maxima at λmax 245, 255, 296, and 344 nm, which is characteristic for a flavonol structure [6]. The IR spectrum showed an absorption for hydroxyl (3423 cm −1 ), conjugated carbonyl (1645 cm −1 ), aromatic (1577 and 1481 cm −1 ), and ether (1132 cm −1 ) groups, respectively [7]. The 13 C-NMR spectrum (Table 1) showing that a methoxyl group was placed at C-6.…”
Section: Resultsmentioning
confidence: 98%
“…The UV spectrum showed absorption maxima at λmax 245, 255, 296, and 344 nm, which is characteristic for a flavonol structure [6]. The IR spectrum showed an absorption for hydroxyl (3423 cm −1 ), conjugated carbonyl (1645 cm −1 ), aromatic (1577 and 1481 cm −1 ), and ether (1132 cm −1 ) groups, respectively [7]. The 13 C-NMR spectrum (Table 1) showing that a methoxyl group was placed at C-6.…”
Section: Resultsmentioning
confidence: 98%
“…The decoction of the leaves of Macaranga recurvata has been used to treat cancer by Dayak people (Tjahjandarie et al, 2019). Previous reports have shown that Macaranga plants produce terpenoids (Qi et al, 2017), flavonoids (Le et al, 2021;Marliana et al, 2018;Tanjung et al, 2010), and stilbenoids (Aldin et al, 2021;Pailee et al, 2015;Tanjung et al, 2018;Yang et al, 2015). Five diterpenoids (cembranoids type), deheiculatins C, and G-J from Macaranga deheiculata showed moderate activity against human 11β-hydroxydehydrogenase type 1 (Qi et al, 2017).…”
Section: Introductionmentioning
confidence: 96%